Promoting a positive image of France. Holiday camps at the service of French foreign and Algerian policy (from 1945 to the mid-1950s). (2nd January 2021) - Fuchs, Julien
ABSTRACT: Since their creation in the 1880s, holiday camps ('colonies de vacances') in France have experienced continued and increasing success. Organised for the most part by local associations or municipalities, they are structured and grouped into federations. A fact specific to France is that the French government took an active role in holiday camps from 1936 onwards. Contributing at first to the democratisation of leisure activities, they went on to become a real public education service after the Second World War, the State then setting up an effective subsidy and inspection system with respect to these camps. Within this context, holiday camps were also considered as important relays of France's foreign and colonial policy, due to their profound symbolic significance. Indeed, they portrayed a picture of a maternal France concerned with the well-being of its children and with national and international solidarity. Between 1945 and the mid-1950s, French holiday camps were then used to serve political and diplomatic agendas. Drawing on ministerial and audiovisual archives, this paper shows, in particular, that holiday camps were promoted abroad in order to further France's international influence, and were widely used to serve the policy established in French Algeria.